4. Muscle excitability in Myotonic Dystrophy type 1. Issue 3 (March 2016) - Boland-Freitas, R.; Howells, J.; Liang, C.; Corbett, A.; Ng, K.
Abstract : The measurement of muscle velocity recovery cycles (MVRCs) is now an established technique that has been used to determine the excitability properties of skeletal muscle in vivo in a variety of myopathic conditions. Patterns of change in the velocity of muscle action potentials generated by different temporal combinations of prior conditioning impulses sensitively reflect membrane polarization and the function of T-tubules. Further, studies in myotonia congenita (MC) have yielded fundamental insights into the function of the muscle chloride channel itself, in both MC and in general. Myotonic dystrophy type 1 (DM1) is an inherited disorder of RNA splicing that alters the transcription of muscle chloride channels, thereby affecting function and causing myotonia. However, a number of other genes encoding muscle proteins that may determine excitability are similarly mis-spliced. We studied the excitability properties of skeletal muscle in DM1, aiming to gain further insight into the determinants of muscle membrane dysfunction in this disorder. Control studies were established and a cohort of DM1 compared to these. The results of the studies will be presented.